Green synthesis of silver nanoparticles and their applications as colorimetric probe for determination of Fe3+ and Hg2+ ions. Issue 5 (12th April 2018) - Azimpanah, Razieh; Solati, Zahra; Hashemi, Majid
Abstract : Silver nanoparticles (AgNPs) were prepared by a green method using Cordia myxa leaf extract. They were characterised by UV–vis spectroscopy, Fourier transform infrared spectroscopy and their X‐ray diffraction pattern. Their sizes were determined by scanning electron micrographs, transmission electron micrographs imaging and dynamic light scattering analysis. The shapes of nanoparticles were spherical or truncated triangular and their average size was determined to be 51.6 nm. Their solution was stable at least for one month. The prepared AgNPs were used as a selective chemical sensor for determination of iron(III) (only when Cl − ions were present in the medium) and mercury(II) ions with detection limits of 0.084 and 0.037 nM, respectively. It was shown that the mechanism of these detections is through oxidation of Ag atoms by Fe 3+ and Hg 2+ ions.